PROBIOTICS ROLE ON IMPROVING MALNUTRITION IN BOTH UNDER- AND OVERWEIGHT CHILDREN: A NARRATIVE REVIEW - Yuniarti, Tricahyani Endah; Piscesa, Saskia; Septiani, Seala; Wijayanti, Elizabeth Anita (Ridwan Institute, 2025)
Background: Malnutrition in children exists at both ends of the spectrum, undernutrition and overnutrition, each with significant health consequences. Probiotics, live microorganisms that confer health benefits when administered in adequate amounts, are being explored as potential interventions through their ability to modulate gut microbiota, enhance nutrient absorption, and regulate immune function. Methods: A narrative review of literatures published between 2004 and 2025 was conducted, covering randomized trials, meta-analyses, and reviews involving probiotics interventions in children. Seventeen key studies were categorized by nutritional status (undernutrition and overnutrition), pediatric health outcomes, and nutritional insights. These studies synthesized and cited into this scientific narration. Results: In undernourished children, probiotics improved weight gain, reduced anemia, enhanced immune responses, and lowered respiratory infection incidence, particularly in low-resource settings. In overweight/obese children, certain Lactobacillus and Bifidobacterium strains improved BMI z-scores and metabolic health. Broader pediatric data support condition-specific benefits of probiotics in gastrointestinal and allergic diseases. Mechanistic evidence highlights bioactive molecules, immune modulation, micronutrient bioavailability, and gut barrier integrity as key pathways. Conclusions: Probiotics have context-specific benefits for pediatric malnutrition, with the strongest evidence in infection reduction and modest growth improvement in undernourished populations. Their role in pediatric obesity is promising but less defined. Strain specificity, dose, and duration remain critical determinants of efficacy, and further high-quality trials are needed.